B(E2) VALUE OF 82Se, 84Kr AND 86Sr ISOTONES FOR N=48 BY USING INTERACTING BOSON MODEL-1. - Islam, Jobaidul; Islam Bhuyan, Md. Didarul; Rahman, Obaydur; Rahman, Md. Habibur (European Scientific Journal, ESJ, 2014)
The reduced transition probability B(E2)↓ of 82Se, 84Kr and 86Sr isotones has been studied by using the Interacting Boson Model-1(IBM-1) . Using this model the reduced transition probabilities B(E2) of these isotones have been calculated for the gamma transition from 8+ → 6+, 6+ → 4+, 4+ → 2+ and 2+ → 0+states. For the first 4+ and 2+ excited states, the excitation energy ratio (R4/2) has been also calculated.